(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: Skin grafting as a reconstructive option in the ladder of closing soft tissue defects is one of the most common procedures available to Plastic surgeons. Graft fixation is critical for the successful survival of a skin graft. Conventional dressing fixation may induce inappropriate pressure and increase wound complications. Negative pressure dressing could be utilized to secure a skin graft and reduce healing time. The objective: Comparison of efficacy and complications between negative pressure dressing and conventional mechanical fixation in skin grafting. Methods and materials: A Comparative Prospective study conducted for the period one year (Jan 2021 – Feb 2022) at Tishreen University Hospital in Lattakia-Syria. The study included two groups of patients were compared: group I consisted of 17 patients (46%) who underwent skin graft fixation with negative pressure dressing, whereas group II consisted of 20 patients (54%) who underwent skin graft fixation with conventional dressing. Results: The recovery time was significantly shorter in the first group (9.41 ± 1.8 vs. 12.68 ± 3.9 in the control group, P-value: 0.001). Bait taking was greater in the first group (88.2%) than in the second group (80%), but without statistical significance (P-value: 0.8). The complication rate in the first group was 17.7% compared to 30% in the second group without significant difference (P-value: 0.7). Factors associated with a longer recovery time in the first group were: smoking (P-value: 0.001) and head and neck defects (P-value: 0.01). While in the second group: smoking (P-value: 0.04), and defects on the trunk (P-value: 0.05). Conclusion: The current study demonstrated favorable results in efficiency of fixing skin grafts with two techniques, with significantly shorter duration of recovery in patients who underwent skin graft fixation with negative pressure dressing compared with the other group.